Linking geographical, agricultural, and dietary factors to human selenium intake and rice selenium concentration: a Taiwanese case study - Kao, P.-T.; Huang, Z.-L.; Mao, H.-J.; Lee, M.R.F.; Wang, S.-L. (Journal of agriculture and food research, 2025)
Selenium (Se) deficiency amongst human populations is common globally, especially among vegetarians and vegans relying solely on soil-uptake by plants. This study aims to evaluate the potential of Se deficiency in plant-based diets and investigate the relationship between Se in locally-grown vegetative food and soil properties. Representative market food produced in different seasons and locations and paddy field rice and soil samples across Taiwan were collected and Se analyzed. Results showed that the vegetative foods in Taiwan generally have higher Se than those in the U.S., but rice Se levels are significantly lower than those reported in the U.S., India, and mainland China. Food type and cultivation location exert greater influence on Se content than seasonal variation. Rice from Northwest Taiwan (Hsinchu and Taoyuan) contains four times more Se than Southeast regions, likely due to lower soil phosphorus (P) and higher iron/aluminum hydroxides, which enhance Se uptake. Over-application of P fertilizers (over 50 % of rice fields have soil M3-P >50 mg kg−1) correlates with reduced Se absorption in rice, as higher soil total P (>1500 mg kg−1) or M3-extractable P (>150 mg kg−1) decreased Se uptake. For vegans in Taiwan, dietary Se intake should be increased roughly fourfold to meet the recommended 55 μg day−1 and stay below toxicity limits of 400 μg day−1. This can be used as a reference for future Se biofortification research for Taiwanese and/or recommendations for inclusion of seaweeds or supplements, ensuring adequate Se intake across dietary preferences, thus improving public health outcomes. [Display omitted] •Vegans in Taiwan risk selenium deficiency; supplements are advised.•Food type and location influence selenium more than seasonal changes.•Regional rice selenium variation is linked to soil Fe oxides and P fertilizers.•Excess P fertilizer reduces rice selenium uptake.